Analysis Of Factors Affecting Accounting Students In Choosing A Career As A Tax Accountant: (Empirical Study on Accounting Students Class of 2019-2020 Narotama University Surabaya) - Ayu Nikmatul Sakdiah; Joko Suyono; Damarsari Ratnasahara Elisabeth (NAROTAMA UNIVERSITY, Indonesia, 2023)
This research was conducted at Narotama University Surabaya. The purpose of the study is to determine and analyze the influence of financial awards, professional recognition, work environment, job market considerations, and social values on the career selection of Narotama University accounting students as tax accountants both simultaneously and partially. The population in this study was 72 students and the sampling in this study used a saturated sample technique with a total sample of 65 respondents. This research uses quantitative methods using a descriptive statistical analysis approach and multiple linear regression analysis. The results of this study show that financial rewards, professional recognition, work environment, job market considerations, and social values have an effect both partially and simultaneously on the career selection of accounting students as tax accountants. The author's advice is good for academics to hold socialization about tax accountant professional associations and improve the educational curriculum regarding accounting study programs so that in the future prospective accounting graduates can become qualified tax accountants.